Understanding early adoption of solar irrigation in Lao PDR: benefits, challenges and policy gaps - Pavelic, Paul; Keovilignavong, O.; Sinavong, P.; Viossanges, Mathieu; Keonouchanh, Santi; Keovongdy, Poupey; Phompackdee, S.; Bounphanousay, D.; Lautze, Jonathan (International Water Management Institute, 2025)
Solar-powered irrigation pumps (SIPs) offer a promising climate-resilient option for farmers, enabling a shift from rainfed to year-round agriculture that can enhance food security and livelihoods. In Laos, SIPs are beginning to be adopted, but the impacts and broader implications of this early uptake remain unclear. This study examines 10 off-grid, smallholder-operated SIPs in the lowlands of Laos to provide evidence for optimal scaling. Interviews were conducted with system operators and complemented by the on-site collection of technical data. Despite high upfront investment costs, most users report strong satisfaction with SIPs. The systems provide reliable irrigation for home consumption, with occasional surpluses sold in markets, and typically achieve payback within five years. Adoption is mainly driven by reductions in fuel and electricity costs, with most systems privately financed. However, broader adoption remains constrained by operational limits under low solar radiation, a lack of government incentives and supportive policies, and limited awareness of potential aggregated impacts on groundwater resources. To support sustainable expansion and reduce investment risks, measures such as capacity building on pump operation, promotion of water-efficient practices, and improved groundwater monitoring are necessary.